1991
DOI: 10.1080/02652039109374035
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir of quinolone residues in fish

Abstract: Different tissues from salmon treated with the quinolones oxolinic acid, flumequine, enrofloxacin and sarafloxacin were analysed in search of possible reservoirs of the drugs. Residues of oxolinic acid and flumequine seem to be especially bound to bone, enrofloxacin to skin, and sarafloxacin to both skin and bone. The results showed that residues of these drugs were present in the fish for prolonged periods after the end of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 4 publications
6
25
1
Order By: Relevance
“…In contrast, very few studies on the pharmacokinetics of the quinolones in fishes treated with multiple doses of medicated feed and reared under field conditions have been carried out (27,32,35). Moreover, previous studies (11) have very seldom taken into consideration the muscle plus the skin matrix and/or the sum of the levels of the enrofloxacin and ciprofloxacin residues in fish tissues.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, very few studies on the pharmacokinetics of the quinolones in fishes treated with multiple doses of medicated feed and reared under field conditions have been carried out (27,32,35). Moreover, previous studies (11) have very seldom taken into consideration the muscle plus the skin matrix and/or the sum of the levels of the enrofloxacin and ciprofloxacin residues in fish tissues.…”
Section: Discussionmentioning
confidence: 97%
“…1b). Some microbiological, metabolism and pharmacokinetic aspects of enrofloxacin have been reported from previous studies with fishes (3,4,11,25,26,29,33); however, very few data on enrofloxacin depletion in fishes reared under field conditions are available (11,32).…”
mentioning
confidence: 99%
“…Previous studies of flumequine pharmacokinetics have also shown an increase of flumequine levels in the terminal depletion phase (Hansen & Horsberg 1999). Steffenak et al (1991) reported an increase in liver oxolinic acid concentration in the late depletion phase after salmon was subjected to stress, and also demonstrated leakage from flumequine reservoirs when the salmon was subjected to cooking (Steffenak et al 1994). Release of flumequine from bone and other reservoirs may therefore explain the small rise in the flumequine level in the terminal depletion phase found in our study.…”
Section: +mentioning
confidence: 99%
“…The affinity of flumequine for skin can be explained by melanin's capacity to bind drugs (Potts 1963, Ullberg et al 1970, Lindquist & Ullberg 1972, Larsson 1993, Fukuda & Sasaki 1994, Howells et al 1994, Salazarbookaman et al 1994. Several studies have reported residues of flumequine and other fluoroquinolones in bone and skin for a long time after the level is below detection in plasma/muscle (Steffenak et al 1991, van der Heijden et al 1993, Elema et al 1994, Martinsen et al 1994.…”
Section: Skin Eye Bilementioning
confidence: 99%
“…According to some reports, fluoroquinolone residues are mainly found in the skin and bones of fish 26 causing considerable damage to articular cartilage and bones of young animals. 27 The mechanism of damage induced by fluoroquinolones to cartilage is unclear.…”
Section: Drug-induced Damage and Recovery In Three Tissues Of A Baeriimentioning
confidence: 99%